Noncompliance and the effects of the minimum wage on hours and welfare in competitive labor markets - Leif Danziger (Institute for the Study of Labor (IZA), 2009)
This paper shows that increases in the minimum wage rate can have ambiguous effects on the working hours and welfare of employed workers in competitive labor markets. The reason is that employers may not comply with the minimum wage legislation and instead pay a lower subminimum wage rate. If workers are risk neutral, we prove that working hours and welfare are invariant to the minimum wage rate. If workers are risk averse and imprudent (which is the empirically likely case), then working hours decrease with the minimum wage rate, while their welfare may increase.
Keywords: J38; 330; Noncompliance; minimum wage; working hours; welfare; competitive labor markets; Mindestlohn; Normbefolgung; Arbeiter; Risikopräferenz; Arbeitszeit; Wohlfahrtseffekt; Arbeitsmarkttheorie; Theorie